2014
DOI: 10.3347/kjp.2014.52.2.183
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Heparin in the Salivary Gland and Midgut of Aedes togoi

Abstract: Mosquitoes secrete saliva that contains biological substances, including anticoagulants that counteract a host's hemostatic response and prevent blood clotting during blood feeding. This study aimed to detect heparin, an anticoagulant in Aedes togoi using an immunohistochemical detection method, in the salivary canal, salivary gland, and midgut of male and female mosquitoes. Comparisons showed that female mosquitoes contained higher concentrations of heparin than male mosquitoes. On average, the level of hepar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 19 publications
(28 reference statements)
1
9
0
Order By: Relevance
“…Another concern that arises with the use of some blood-contacting biomedical devices is the increased risk that thrombosis may occur and lead to adverse conditions and higher patient morbidity and mortality [56]. In contrast to medical devices devoid of anticoagulant agents, the mosquito proboscis, upon insertion into the body, excretes salvia enriched with proteins that inhibit clotting events that would otherwise occur as a response to the endothelial damage [5][6][7][8][9][10][11]57]. Due to their antihemostatic properties, these mosquito salivary proteins could serve as prospective candidates for integration into blood-contacting biomaterials to prevent clot formation and device rejection.…”
Section: Mosquito-derived Polymers With Anticoagulant Propertiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Another concern that arises with the use of some blood-contacting biomedical devices is the increased risk that thrombosis may occur and lead to adverse conditions and higher patient morbidity and mortality [56]. In contrast to medical devices devoid of anticoagulant agents, the mosquito proboscis, upon insertion into the body, excretes salvia enriched with proteins that inhibit clotting events that would otherwise occur as a response to the endothelial damage [5][6][7][8][9][10][11]57]. Due to their antihemostatic properties, these mosquito salivary proteins could serve as prospective candidates for integration into blood-contacting biomaterials to prevent clot formation and device rejection.…”
Section: Mosquito-derived Polymers With Anticoagulant Propertiesmentioning
confidence: 99%
“…Anopheline antiplatelet protein (AAPP), CPP protein (derived from Culex pipiens pallens), Aegyptin, hamadarin, and even heparin itself are all biological molecules contained in the saliva of different mosquito species that aid in the ingestion of a blood meal by interfering with the host clotting cascade or platelet aggregation [5][6][7][8][9][10][11]57]. These biomolecules can either directly bind to collagen, preventing its adhesion to platelets, or can inhibit one or more factors in the coagulation cascade.…”
Section: Mosquito-derived Polymers With Anticoagulant Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The subsequent short rise in voltage level (emf) at higher Ri levels shows maintenance of electrical contact. We hypothesize that analgesic, anti-coagulant saliva secreted on the skin surface could mask insertion of the stylets into the human host James 1995, 1996;Ha et al 2014).…”
Section: Biological Meanings Of Mosquito Epg Waveformsmentioning
confidence: 99%
“…During a subsequent blood meal, the infectious mosquito inoculates virus and insect-derived molecules, including salivary components, into the dermis of a new human host. The saliva from hematophagous mosquitoes is a cocktail of pharmacologically active molecules, some of which are anti-hemostatic, angiogenic, and immunomodulatory [5][6][7] . Over the last couple decades, several animal and in vitro studies demonstrated that inoculation of vector saliva, and/or concomitant blood-feeding by an arthropod, can immunomodulate the host antiviral response in the skin and periphery [7][8][9][10] .…”
Section: Introductionmentioning
confidence: 99%